2022
DOI: 10.3389/fimmu.2021.822345
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptor Kinase 2 as Novel Therapeutic Target in Fibrotic Diseases

Abstract: G protein-coupled receptor kinase 2 (GRK2), an important subtype of GRKs, specifically phosphorylates agonist-activated G protein-coupled receptors (GPCRs). Besides, current research confirms that it participates in multiple regulation of diverse cells via a non-phosphorylated pathway, including interacting with various non-receptor substrates and binding partners. Fibrosis is a common pathophysiological phenomenon in the repair process of many tissues due to various pathogenic factors such as inflammation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 124 publications
2
4
0
Order By: Relevance
“…Regarding macrophages, we discovered that the SPP1/C1QC dichotomy of macrophages was more reasonable than the classic M1/M2 classification in CC, further supporting previous studies. [ 30,41 ] In terms of DCs, we identified that CLEC9A+ DCs exerted positive antigen presentation, while LAMP3C+ DCs were related to apoptosis, which implied a mature and exhaustion‐like functional state concordant with previous researches. [ 42,43 ] Notably, we discovered CD8+ T ex cells expressing immune checkpoints, including not only PDCD1 but also TIGIT and CD96 , which have already aroused great interests as novel immune checkpoint targets.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding macrophages, we discovered that the SPP1/C1QC dichotomy of macrophages was more reasonable than the classic M1/M2 classification in CC, further supporting previous studies. [ 30,41 ] In terms of DCs, we identified that CLEC9A+ DCs exerted positive antigen presentation, while LAMP3C+ DCs were related to apoptosis, which implied a mature and exhaustion‐like functional state concordant with previous researches. [ 42,43 ] Notably, we discovered CD8+ T ex cells expressing immune checkpoints, including not only PDCD1 but also TIGIT and CD96 , which have already aroused great interests as novel immune checkpoint targets.…”
Section: Discussionsupporting
confidence: 87%
“…GRK2 plays a key role in the development of many cardiovascular diseases [16]. High levels of cardiac GRK2 are associated with the induction of cardiac hypertrophy and fibrosis [20,37]. Consistently, in this study, the ISO-induced CH model showed a significant increase in GRK2 expression.…”
Section: Discussionsupporting
confidence: 87%
“…The C1QC+/SPP1+ tumor‐associated macrophage (TAM) dichotomy was first noted in colorectal cancer (CRC) by Lei Zhang et al [ 29 ] and it was confirmed by Xiong Li et al that this dichotomy could discriminate cervical cancer patients with different prognoses. [ 48 ] Thus, it was feasible to apply this ubiquitous macrophage classification in our study. C1QC+ TAMs were reported to play roles in immunosurveillance, while SPP1+ TAMs played a protumorigenic/prometastatic role in tumors.…”
Section: Discussionmentioning
confidence: 99%